A Forensic-Ready Virtual Currency Reward Framework for Metaverse-Based Work Environments - Robertson, Shelley-Anne; Baror, Stacey Omeleze; Venter, Hein Salomon (The Indonesian Journal of Computer Science, 2026)
As immersive and distributed work environments expand within metaverse platforms, organisations face increasing challenges in maintaining trust, accountability, and integrity in digital reward systems. Virtual currency–based incentives offer flexibility and scalability but introduce risks related to integrity, dispute resolution, and evidentiary reliability. Existing approaches often rely on blockchain immutability alone, which is insufficient to support proactive preservation of digital evidence within reward systems. This paper proposes a forensic-ready architectural framework for virtual currency–based organisational reward systems, in which Digital Forensic Readiness is embedded as a core system design principle rather than a post-hoc security layer. The Metaward framework integrates motivational event instrumentation, forensic logging, traceability, and governance mechanisms to generate verifiable digital traces during normal operation. A conceptual instantiation and scenario-based analysis, supported by an illustrative proof-of-concept instantiation, demonstrate the feasibility of the proposed approach within metaverse-based work environments.